The Activity Of Posyandu Cadres At Healt Center Siulak Mukai Kerinci Regency - Rumita Ena Sari; Adila Solida; Atik Maria; Shafira Ainun Hafilda (CV. AFDIFAL MAJU BERKAH, 2022)
Posyandu is one form of community-sourced health efforts, which is managed from, by, for and with the community. Based on data from the Kerinci regency Health Office in 2020-2021, it was found that in kerinci regency there were 21 health centers with 293 posyandu and only 61 Posyandu were active, in the profile of the siulak mukai Health Center in 2020-2021 there were 14 posyandu and only 1 posyandu was active with a cadre of 70 people. This research is a quantitative research with cross sectional design. The sample is a whole cadre of 70 people. Data collection was carried out from March 2022 to April 2022. Data were collected using questionnaires that have been tested for validity and reliability. Data analysis with multiple logistic regression test. There were (p=0.001) PR=469 (95% CI=302-727) motivation award (p=0.001) PR=2,540(95% CI=1,3184.892) motivation reward (p=0.000) PR=2,583 (95% CI=1,400-4,767)with cadre activity. There was no relationship between age (p=1,000) PR=0.866 (95% CI=567-1, 325) marital status (p=0.974) PR=0.877 (95% CI=490-1, 571) occupation (p=0.788) PR=1.121 (95% CI=720-1, 747) length of Service (p=0.501) PR=1.246 (95% CI=765 - 2,028) responsibility (P=0,133) PR=2,190 (95% CI=1,458-3,290) interpersonal relationships (P=308) PR=1,308 (95% CI=860-1, 990) with cadre activeness. Based on the results of multivariate tests, it is known that the education variable has a significant relationship with the p value (0.038), and has a value of B (1.074) and the value of OR 2.928 is the highest when compared with other variables. These results show that education is the most dominant variable that affects the activity of cadres.Education variable is the most dominant variable that affects the activity of cadres. It is expected that the Healt Center Siulak Mukai pay attention to the level of education of cadres during recruitment. For posyandu cadres to better carry out posyandu activities in accordance with their duties and responsibilities and are expected to be more active in visiting people's homes to continue to monitor their health and motivate them to take advantage of posyandu.